KEY ISSUE II. ANTI-SMOKING ACTIVITIES. (Tufts Archival Research Center, 2007)
Report on key issues surrounding anti-smoking activities highlighting the industry objective to change the public's attitude towards smoking and aggressively combat the regulatory threats and problems. Includes information on smoking and health, social acceptability of smoking, taxation and bands, and marketing and product restraints.